PENTINGNYA PERAN ORANG TUA DALAM DUNIA PENDIDIKAN ANAK - Tony Wibowo; Edo Lee; Jeslyn Jeslyn; Joy Christian Tedjo; Leslyn Kho; Nercy Hanty; Sherly Ozella; Slin Slin`; Stefanie Stefanie; Vera Novilia; Vindriyanto Vindriyanto (National Conference for Community Service Project (NaCosPro), 2020)
The quality of education of the Indonesian state is not so good, so the human resources produced are not very good. Improving the quality of education in Indonesia can be done in early childhood, with the help of parents. In other words, parents take part in the education of their children. Although not the only factor that can improve the quality of education, the role of parents in the world of children's education has a great impact so that it can bring changes to the quality of education. There are still many parents who don't realize how important their role is in the world of education. The formation of comics aimed at parents is an alternative that can be used to raise awareness in parents that their role is very important for their children's lives, especially in the world of education.